A Comparison of Brain Activity between Healthy Subjects and Stroke Patients on fMRI by Acupuncture Stimulation - Cho, Seung-Yeon; Kim, Mia; Sun, Jong Joo; Jahng, Geon-Ho; Kim, Hengjun J.; Park, Seong-Uk; Jung, Woo-Sang; Ko, Chang-Nam; Park, Jung-Mi (Chinese journal of integrative medicine, 2013)
Objective： To investigate brain activity patterns during acupuncture in stroke patients, and to compare the result with normal subjects using functional magnetic resonance imaging （fMRI）. Methods： A total of 11 stroke patients with motor weakness and 10 healthy subjects were studied, fMRI was performed during acupuncture on the left side at points Quchi （Llll） and Zusanli （ST36）. Data were analyzed using statistical parametric maps of brain activation induced by acupuncture stimulation. Results： The results showed that stimulation of both LI11 and ST36 produced significantly different brain activation patterns between the two groups. The normal group showed a greater overall activation than the stroke group. In the normal group, parts of the frontal lobe, parietal lobe, sub-lobar, cerebellum and midbrain regions were activated by acupuncture at the left LI11. On the other hand, only the right side of the inferior parietal Iobule region was activated in the stroke patients. When the left ST36 was stimulated in the normal group, both sides of the frontal lobe, parietal lobe, temporal lobe, and sub-lobar, and the left side of occipital lobe, and the right side of cerebellum and midbrain regions were activated. For the same stimulation in the stroke group, only both sides of the inferior parietal Iobule and cerebellum regions were activated （P〈0.05, cluster level）. Deactivation pattern was not noted during any acupuncture stimulation in both groups. Conclusion： Brain signal activations during the same acupuncture were different between the healthy and the stroke patients, and the effects showed a correlation of different acupuncture points.